PO122 Therapeutic plasma exchange for neurological disorders associated with anti-vgkc antibodies. (1st December 2017) - Das, Joyutpal; Tan, Maevis; Matthews, Rachael; Lilleker, James B; Gosal, David; Sharaf, Nazar
Abstract : Background: Antibodies against the voltage-gated potassium channel (VGKC) complex are typically associated with neuromyotonia, Morvan's syndrome, limbic encephalitis and epilepsy. The exact role and efficacy of therapeutic plasma exchange (TPE) in such disorders is unclear. We report our experience of using TPE in this setting. Methods: We retrospectively reviewed the medical records of 11 patients with anti-VGKC antibodies associated disorders receiving TPE at the Greater Manchester Neuroscience Centre from 2012–2015. Results: The median age was 62 years. Their clinical features include seizure, confusion, cognitive decline, rigidity, muscle cramp, myokymia, altered sensation and hallucination. Brain MRI was abnormal in five patients. CSF analysis showed raised protein in five and lymphocytic pleocytosis in one. The median anti-VGKC antibody titre was 3310 pM. In addition, IVIg was used in three patients. All received corticosteroids and subsequent choice of steroid-sparing agent was rituximab, azathioprine, mycophenolate or methotrexate. A sustained favourable response to TPE was observed in eight cases. There was no response in three and only one had transient response. Conclusion: This retrospective study suggests that TPE for neurological disorders associated with anti-VGKC antibodies have high rates of favourable response, which is consistent with previous studies. Prospective controlled studies are required to confirm this.